2018
DOI: 10.1096/fj.201701480r
|View full text |Cite
|
Sign up to set email alerts
|

Smad ubiquitylation regulatory factor 1 promotes LIM‐homeobox gene 9 degradation and represses testosterone production in Leydig cells

Abstract: Testosterone is essential for spermatogenesis and the maintenance of secondary sexual characteristics in males. An important transcription factor, LIM-homeobox gene 9 (Lhx9) is indispensable for testis development and testosterone production; however, post-translational modifications of Lhx9 are largely unknown. Here, for the first time to our knowledge, we demonstrate that the level of Lhx9 protein increases in human chorionic gonadotropin-exposed Leydig cells and can be polyubiquitylated. We found that Smad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…If there is an altered differentiation of luteal cells in the Lhx9 +/ovary, this may impact the expression of cholesterol and steroidrelated genes. Lhx9 expression in the steroidal cells of the male Leydig cells has been shown previously 40,41 , thus the expression of Lhx9 shown here in the steroidal corporal lutea may reflect a function in the differentiation of steroidogenic cells.…”
Section: Examining Lhx9 Expression To Inform Functionsupporting
confidence: 74%
“…If there is an altered differentiation of luteal cells in the Lhx9 +/ovary, this may impact the expression of cholesterol and steroidrelated genes. Lhx9 expression in the steroidal cells of the male Leydig cells has been shown previously 40,41 , thus the expression of Lhx9 shown here in the steroidal corporal lutea may reflect a function in the differentiation of steroidogenic cells.…”
Section: Examining Lhx9 Expression To Inform Functionsupporting
confidence: 74%
“…Testosterone (T), a steroid hormone, produced mainly by LCs [26], is of vital importance to the development and function of male reproduction, and to the maintenance of normal spermatogenesis [27]. Shahin [10] reported that 1800 MHz RF exposure (1.15 W/m 2 , 3 h/day for 120 days) acted in the male reproductive tract of mice, in part by inhibiting T secretion from LCs.…”
Section: Discussionmentioning
confidence: 99%
“…Smurf1 wild‐type and KO male mice were fed with a standard chow diet (CD) or high‐fat diet (HFD) (Research Diets, Cat# D12492 with 60 kcal% fat) for 19 weeks at the age of 4 weeks. Mice maintenance and HFD modeling were performed as described previously 15,16 . Mice feeding metabolism was analyzed using metabolic cages (TSE Systems GmbH, Bad Homburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Mice maintenance and HFD modeling were performed as described previously. 15,16 Mice feeding metabolism was analyzed using metabolic cages (TSE Systems GmbH, Bad Homburg, Germany). Mice were tested for 1 week and data from Days 5 to 7 were analyzed.…”
Section: Animal Experimentationmentioning
confidence: 99%